EKSPERIMEN MODEL PROCESS ORIENTED GUIDED INQUIRY LEARNING BERBASIS SOCIO SCIENTIFIC ISSUE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA MATERI PENCEMARAN LINGKUNGAN - Riannisa'a Shafira; Nurmiyati Nurmiyati; Alanindra Saputra (Biosfer: Jurnal Pendidikan Biologi, 2026)
Critical thinking is a core 21st-century competency; however, evidence shows that many Indonesian students struggle with higher-order cognitive tasks. In a Surakarta public high school, over 50% of the Grade 10 students answered C3–C6 biology items incorrectly. The average student score represents 62.86, which falls below the minimum passing grade of 75. This significant gap indicates that lecture-based instruction provides insufficient support for student learning. This study examined the effectiveness of integrating Socio-Scientific Issues (SSI) into Process-Oriented Guided Inquiry Learning (POGIL) to improve students' critical thinking on environmental pollution. A quantitative quasi-experimental pretest–posttest design was applied to two homogeneous classes (n=36 each) selected from a total of 324 students: an experimental class receiving SSI-based POGIL and a control class receiving conventional instruction. Critical thinking was measured using a validated 10-item essay test with five indicators, supported by observations, interviews, and document analysis. Analyses were conducted using SPSS and N-gain software. The experimental class achieved a higher mean critical thinking score than the control class (89.4 vs. 56.6), with significant pre–post improvement in the experimental group (p=0.00<0.05) but not in the control group (p=0.20). The SSI-based POGIL implementation strongly correlated with critical thinking gains (r=0.835; p=0.000) and yielded a high N-gain (0.76). Observations showed the strongest performance in concluding with evidence (2.67/3.00) and a weaker performance in interpreting problems using local pollution cases over three 80-minute meetings. These findings indicate that SSI-based POGIL can enhance critical thinking in environmental pollution learning, although generalizability is limited by the small sample size.